The Abilities of Endophytic and Biofertilizing Bacteria and Their Combinations to Suppress Bacterial Wilt Disease (Ralstonia solanacearum) of Chili - Istifadaha, Noor; Ningtyasb, Dewi Nurma Yanti; Suryatmana, Pujawati; Fitriatin, Betty Natalie (KnE Life Sciences, 2017)
Bacterial wilt disease (Ralstonia solanacearum) is one of the most important diseases in Solanaceae, including chili. Biological control is one of environmentally-friendly method for controlling plant diseases. Microbes that are potential as biological control agents include bacterial endophytes and bacteria that are usually used as biofertilizer. This paper discusses the result of the study that examined the abilities of endophytic and biofertilizing bacteria solely or in combination to suppress bacterial wilt disease (R. solanacearum). The endophytic bacteria isolates tested were Lysinibacillus sp. and Bacillus subtilis, while biofertilizing bacteria used were N-fixing bacteria (Azotobacter chrococcum) and P-solubilizing bacteria (Pseudomonas cepacea). The results showed that the endophytic bacteria, biofertilizing bacteria and their combination inhibited wilt disease incidence in chili by 46.7-80 %. The highest disease suppression (80 %) showed by the endophytic bacteria, B. subtilis. This endophyte was also able to promote a significant chili growth. Keywords: Ralstonia solanacearum, Endophytic bacteria, Biofertilizer, Biological control, Chili.